Spectrophotometric Determination of Chlorpromazine Hydrochloride Using 4-Nitroanilline by Oxidative Coupling Reaction - Al-rashidy et al. (مجلة بغداد للعلوم, 2019)
A simple, rapid spectrophotometric method has been established for the determination of chlorpromazine hydrochloride (CPZ) in its pure form and in a tablet formulations. The  suggested  method  is  based  on  the  oxidative coupling  reaction  with4-nitroainlline using KIO3 in acidic solution to produce a violet colored product with maximum absorption at λ=526 nm.The  analytical data  obtained  throughout  this  study  could  be  summarid  as  follows:  1ml of 1M HCl (pH=2.2), 1 ml  of  4-nitroanilline (1x10-2M), and 1.5ml  of (1x10-2)KIO3 per 25 ml reaction medium. The order of additions, coupling reaction time, and temperature in addition to the type of solvent were studied.